Valorization and Destruction: Colonial Buildings in Lagos State, Nigeria, as Sites of Contestation - Tokie Laotan-Brown (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Colonial architecture in Lagos State, Nigeria, represents enduring legacies of domination, but these structures are also sites of shifting meanings as different groups engage with their past. This paper examines the dual processes of valorization and destruction of colonial buildings, considering the role of communities and stakeholders in defining the value of inherited spaces. Colonial-era landmarks, such as the Lagos Glover Hall, have undergone processes of valorization, often reflecting an attempt to reimagine and adapt these sites for contemporary use. In their transformation into cultural centers or heritage sites, these buildings are valorized, attempting to preserve colonial architectural aesthetics while stripping them of their original oppressive connotations.Conversely, the demolition of other colonial structures, such as former government buildings in Ikoyi and Marina, represents both a literal and symbolic destruction of the colonial past. The erasure of these structures is influenced by broader societal desires to reshape Lagos’s urban landscape and sever the visible ties to foreign domination. This duality illustrates the notion of “multiple material traces,” where colonial remnants serve as both cultural heritage and as contested symbols of oppression.The paper also considers the emerging voices within architectural communities in Nigeria demanding genuinely decolonial approaches to the built environment. These movements challenge the valorization of colonial legacies and advocate for new architectural forms that foreground local narratives, materials, and traditions. The interaction between valorization and destruction highlights the complex processes at play in reshaping the urban fabric of Lagos—a city that continues to grapple with its colonial past while envisioning a future grounded in traditional cultural expression and architectural autonomy. Through a critical analysis of specific case studies, this paper investigates how representations of these inherited architectures differ and what values and transformations are at stake in their ongoing reimagination.